Negative pole piece of secondary battery, preparation method and secondary battery

By depositing a solid composite film consisting of a first inorganic layer, a polymer layer, and a second inorganic layer on the surface of the negative electrode active material layer of a secondary battery, the problems of unevenness and poor stability of the SEI film are solved, the cycle life and coulombic efficiency of the battery are improved, and the safety of the battery is enhanced.

CN121002669APending Publication Date: 2025-11-21NANTONG MORLUS TECHNOLOGY CO LTD

Patent Information

Application Number
CN202580001980.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-29
Publication Date
2025-11-21

AI Technical Summary

Technical Problem

In existing secondary batteries, the naturally formed SEI film has uneven composition and poor mechanical stability, resulting in short battery cycle life and low coulombic efficiency.

Method used

A solid composite film consisting of a first inorganic layer, a polymer layer, and a second inorganic layer is deposited on the surface of the negative electrode active material layer. The layers are connected by chemical bonds. The film is prepared by atomic layer deposition and molecular layer deposition to form an organic-inorganic mixed multilayer artificial SEI film.

Benefits of technology

It improves the mechanical strength and chemical stability of the battery, optimizes the ion transport path, reduces interface impedance, and enhances the battery's cycle life, coulombic efficiency, and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121002669A_ABST
    Figure CN121002669A_ABST
Patent Text Reader

Abstract

In order to solve the problems of short cycle life and low coulombic efficiency of the secondary battery caused by non-uniform components and poor mechanical stability of a naturally formed SEI film in the prior art, the invention provides the negative electrode plate of the secondary battery, the preparation method and the secondary battery. A solid composite film layer is deposited on the surface of a negative active substance layer of the negative pole piece of the secondary battery, the solid composite film layer comprises a first inorganic layer, a polymer layer and a second inorganic layer, and all the layers of the solid composite film layer are connected through chemical bonds.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application relates to the technical field of secondary batteries, in particular to a negative electrode sheet of a secondary battery, a preparation method and a secondary battery. BACKGROUND

[0002] As a high-efficiency energy storage device, secondary batteries have been widely used in the fields of consumer electronics, electric vehicles and renewable energy storage. However, the performance and service life of the secondary batteries depend largely on the quality and stability of the solid electrolyte interface (SEI) film on the negative electrode surface. The SEI film is a passivation film naturally formed in the reaction process of the electrode material and the electrolyte, and it plays a key role in the battery cycle process: it can prevent the direct contact between the electrolyte and the negative active material, prevent side reactions, and allow lithium ions to pass through to realize the charging and discharging process of the battery. However, the naturally formed SEI film usually has problems such as uneven composition, poor mechanical stability and insufficient electrical conductivity, which significantly affect the cycle life and safety of the battery.

[0003] To overcome these shortcomings, recent research has focused on depositing a solid composite film layer with optimized performance on the surface of the negative active material layer through artificial methods, i.e. artificial SEI film layer. This artificial SEI film layer aims to improve the chemical stability, mechanical strength and ionic conductivity of the negative electrode interface, thereby significantly improving the battery performance. For example, the article "Reversible High-Capacity Si Nanocomposite Anodes for Lithium-ion Batteries Enabled by Molecular Layer Deposition" proposes to use an artificial SEI film to enhance the mechanical stability and chemical uniformity of the SEI film through surface coating technology. In particular, the inorganic-organic hybrid coating prepared by the molecular layer deposition (MLD) technology is considered to be an effective solution to the volume change and SEI film failure. These coatings not only alleviate the volume expansion of the nano-silicon negative electrode material, but also inhibit the generation of dendrites, improving the cycle stability of the battery. However, each layer in this scheme is a single-layer structure, which may have defects at some positions of each layer, making it possible that inorganic-inorganic-inorganic-organic may occur at some positions of the coating. This leads to defects such as unevenness and incompleteness in the entire coating. In addition, the single-layer (single-cycle) organic layer has poor flexibility and is difficult to adapt to different situations. The flexible adjustment (multiple cycles) of the thickness, structure and composition of the polymer in this scheme can adjust the flexibility and adapt to different situations.

[0004] For example, the US patent application No. US14138267 discloses a study on the construction of multifunctional composite coating on the surface of the negative electrode of a battery by atomic layer deposition (ALD) technology. This coating can form a protective film with precise thickness control and uniform coverage by layer-by-layer deposition of inorganic materials. ALD technology is widely used in secondary batteries to improve the chemical stability of the electrode and electrolyte interface, prevent corrosion and side reactions of the electrode material, and improve the cycle life and coulombic efficiency of the electrode. However, the inorganic layer in this scheme has poor flexibility, and the composite coating is prone to cracking, which leads to poor performance (cycle life, coulombic effect) control of the battery. SUMMARY

[0005] In view of the poor cycle life and low coulombic efficiency of the secondary battery caused by the uneven composition and poor mechanical stability of the naturally formed SEI film in the prior art, the present application provides a negative electrode sheet for a secondary battery, a preparation method and a secondary battery.

[0006] To achieve the above-mentioned purpose, the present application provides the following technical solutions: In a first aspect, the present application provides a negative electrode sheet for a secondary battery, which comprises a solid composite film layer deposited on the surface of a negative active material layer, the solid composite film layer comprising a first inorganic layer, a polymer layer and a second inorganic layer, and each layer of the solid composite film layer being connected by a chemical bond.

[0007] Further, the thickness of the first inorganic layer is 0.1 nm-80 nm, the thickness of the polymer layer is 0.4 nm-100 nm, and the thickness of the second inorganic layer is 0.1 nm-80 nm.

[0008] Further, the thickness of the first inorganic layer is 0.5 nm-20 nm, the thickness of the polymer layer is 2 nm-60 nm, and the thickness of the second inorganic layer is 0.5 nm-20 nm.

[0009] Further, the second inorganic layer further comprises a repeating unit composed of the polymer layer and the inorganic layer on the upper surface, and the repeating unit is 1-50.

[0010] Further, the first inorganic layer and / or the second inorganic layer comprises an oxide selected from the following metals: aluminum (Al), titanium (Ti), silicon (Si), tin (Sn), vanadium (V), zirconium (Zr), zinc (Zn), lithium (Li), sodium (Na), potassium (K), niobium (Nb), tungsten (W), molybdenum (Mo) or a combination thereof.

[0011] Further, the first inorganic layer and / or the second inorganic layer comprises one of the following oxides: aluminum oxide (AI2O3), titanium dioxide (TiO2), silicon dioxide (SiO2), tin dioxide (SnO2), vanadium pentoxide (V2O5), zirconium dioxide (ZrO2), zinc oxide (ZnO), lithium oxide (Li2O), lithium superoxide (LiO2), sodium oxide (Na2O), sodium superoxide (NaO2), potassium oxide (K2O), potassium superoxide (KO2), niobium pentoxide (Nb2O5), tungsten trioxide (WO3), molybdenum trioxide (MoO3).

[0012] Further, the second inorganic layer comprises one of the following compounds: fluoride, oxide, carbide, and nitride.

[0013] Further, the first inorganic layer and the second inorganic layer each comprise a thin layer of aluminum oxide (AI2O3).

[0014] Further, the second inorganic layer comprises a thin layer of aluminum fluoride (AIF3).

[0015] Further, the polymer layer is formed by polymerization of a monomer having multiple functional groups.

[0016] Further, the monomer is selected from the following monomers: terephthaloyl chloride, ethylene glycol, terephthalamide, terephthaldehyde, terephthalic acid, p- phenylenediamine, hydroquinone, p-chlorobenzene, p-dinitrobenzene, 2,4- dinitroaniline, 4-4'-diaminodiphenyl ether, 4-4'-dihydroxydiphenyl ether, 4-4'- dicarboxydiphenyl ether, 4-4'-dichlorodiphenyl ether, ethylenediamine, oxalic acid, glyoxal, 1,2-dichloroethane, malonyl chloride, pyromellitic dianhydride, and derivatives of the above.

[0017] Further, the monomer is terephthaloyl chloride and ethylene glycol.

[0018] Further, the monomer is terephthaloyl chloride and p-phenylenediamine.

[0019] Further, the monomer is ethylene glycol and p-phenylenediamine.

[0020] Further, the monomer is terephthaloyl chloride, ethylene glycol, and p- phenylenediamine.

[0021] Further, an active group is formed on the surface of the negative electrode active material layer, and the active group is chemically bonded to the first inorganic layer.

[0022] Further, the active group comprises one of the following groups: hydroxyl (-OH), carboxyl (-COOH), amino (-NH2), aldehyde (-CHO), and nitro (-NO2).

[0023] Further, the active group is a hydroxyl group (-OH).

[0024] Further, the negative active material layer comprises one of the following negative active materials: graphite, hard carbon, silicon-carbon composite, silicon-oxygen-carbon material composite, silicon, lithium metal, lithium titanium oxide, silicon-based alloy, tin-based alloy, lithium-based alloy (such as lithium-silver alloy), copper or copper-based alloy, or a combination thereof.

[0025] Further, the negative active material used in the negative active material layer comprises graphite.

[0026] Further, the negative active material used in the negative active material layer comprises silicon-carbon composite or silicon-oxygen-carbon material composite.

[0027] Further, the negative active material used in the negative active material layer comprises silicon.

[0028] Further, the negative active material used in the negative active material layer is lithium metal.

[0029] In a second aspect, the present application also provides a method for preparing a negative electrode sheet of a secondary battery, the negative electrode sheet comprising a negative active material layer, and a solid composite film layer deposited on the surface of the negative active material layer by the following steps: S1. introducing active groups on the surface of the negative active material layer by chemical treatment; S2. forming a first inorganic layer on the active groups by atomic layer deposition; S3. forming a polymer layer on the upper surface of the first inorganic layer by molecular layer deposition; and S4. forming a second inorganic layer on the upper surface of the polymer layer by atomic layer deposition.

[0030] Further, in step S1, the active groups introduced on the surface of the negative active material layer by chemical treatment are selected from one of the following groups: hydroxyl group (-OH), carboxyl group (-COOH), amino group (-NH2), aldehyde group (-CHO), and nitro group (-NO2).

[0031] Further, in step S1, the chemical treatment is a micro-oxidation treatment on the surface of the negative active material layer to introduce hydroxyl active groups.

[0032] Further, in step S1, the micro-oxidation treatment method is plasma oxidation method.

[0033] Further, in step S1, the micro-oxidation treatment method is oxidant oxidation method, and the oxidant used is hydrogen peroxide solution.

[0034] Further, in step S2, the first inorganic layer is prepared by atomic layer deposition (ALD) using water vapor (H2O) and trimethylaluminum (TMA) gas.

[0035] Further, in step S2, the first inorganic layer is prepared by atomic layer deposition (ALD) using water vapor (H2O) and trimethylaluminum (TMA) gas.

[0036] Further, in step S2, the first inorganic layer is prepared by atomic layer deposition (ALD) using water vapor (H2O) and trimethylaluminum (TMA) gas.

[0037] Further, in step S3, the polymer layer is prepared by molecular layer deposition (MLD) using a monomer with multiple functional groups; the monomer is selected from the following monomers: terephthaloyl chloride, ethylene glycol, terephthalamide, terephthaldehyde, terephthalic acid, p-phenylenediamine, hydroquinone, p-chlorobenzene, p-dinitrobenzene, 2,4-dinitroaniline, 4-4'-diaminodiphenyl ether, 4-4'-dihydroxydiphenyl ether, 4-4'-dicarboxy diphenyl ether, 4-4'-dichlorodiphenyl ether, ethylenediamine, oxalic acid, glyoxal, 1,2-dichloroethane, malonyl chloride, pyromellitic dianhydride, and derivatives of the above substances.

[0038] Further, in step S3, the polymer layer is prepared by molecular layer deposition (MLD) using a monomer with multiple functional groups; the monomer is selected from the following monomers: terephthaloyl chloride, ethylene glycol, terephthalamide, terephthaldehyde, terephthalic acid, p-phenylenediamine, hydroquinone, p-chlorobenzene, p-dinitrobenzene, 2,4-dinitroaniline, 4-4'-diaminodiphenyl ether, 4-4'-dihydroxydiphenyl ether, 4-4'-dicarboxy diphenyl ether, 4-4'-dichlorodiphenyl ether, ethylenediamine, oxalic acid, glyoxal, 1,2-dichloroethane, malonyl chloride, pyromellitic dianhydride, and derivatives of the above substances.

[0039] Further, in step S3, the polymer layer is prepared by molecular layer deposition (MLD) using a monomer with multiple functional groups; the monomer is selected from the following monomers: terephthaloyl chloride, ethylene glycol, terephthalamide, terephthaldehyde, terephthalic acid, p-phenylenediamine, hydroquinone, p-chlorobenzene, p-dinitrobenzene, 2,4-dinitroaniline, 4-4'-diaminodiphenyl ether, 4-4'-dihydroxydiphenyl ether, 4-4'-dicarboxy diphenyl ether, 4-4'-dichlorodiphenyl ether, ethylenediamine, oxalic acid, glyoxal, 1,2-dichloroethane, malonyl chloride, pyromellitic dianhydride, and derivatives of the above substances.

[0040] Further, in step S3, the polymer layer is prepared by molecular layer deposition (MLD) using a monomer with multiple functional groups; the monomer is selected from the following monomers: terephthaloyl chloride, ethylene glycol, terephthalamide, terephthaldehyde, terephthalic acid, p-phenylenediamine, hydroquinone, p-chlorobenzene, p-dinitrobenzene, 2,4-dinitroaniline, 4-4'-diaminodiphenyl ether, 4-4'-dihydroxydiphenyl ether, 4-4'-dicarboxy diphenyl ether, 4-4'-dichlorodiphenyl ether, ethylenediamine, oxalic acid, glyoxal, 1,2-dichloroethane, malonyl chloride, pyromellitic dianhydride, and derivatives of the above substances.

[0041] Further, in step S3, the polymer layer is prepared by molecular layer deposition (MLD) using a monomer with multiple functional groups; the monomer is selected from the following monomers: terephthaloyl chloride, ethylene glycol, terephthalamide, terephthaldehyde, terephthalic acid, p-phenylenediamine, hydroquinone, p-chlorobenzene, p-dinitrobenzene, 2,4-dinitroaniline, 4-4'-diaminodiphenyl ether, 4-4'-dihydroxydiphenyl ether, 4-4'-dicarboxy diphenyl ether, 4-4'-dichlorodiphenyl ether, ethylenediamine, oxalic acid, glyoxal, 1,2-dichloroethane, malonyl chloride, pyromellitic dianhydride, and derivatives of the above substances.

[0042] Further, in step S3, the polymer layer is prepared by molecular layer deposition (MLD) using a monomer with multiple functional groups; the monomer is selected from the following monomers: terephthaloyl chloride, ethylene glycol, terephthalamide, terephthaldehyde, terephthalic acid, p-phenylenediamine, hydroquinone, p-chlorobenzene, p-dinitrobenzene, 2,4-dinitroaniline, 4-4'-diaminodiphenyl ether, 4-4'-dihydroxydiphenyl ether, 4-4'-dicarboxy diphenyl ether, 4-4'-dichlorodiphenyl ether, ethylenediamine, oxalic acid, glyoxal, 1,2-dichloroethane, malonyl chloride, pyromellitic dianhydride, and derivatives of the above substances.

[0043] Further, the monomers are terephthaloyl chloride, ethylene glycol and p-phenylenediamine, and the terephthaloyl chloride, ethylene glycol and p-phenylenediamine are polymerized into a poly(p-phenyleneterephthalamide) thin layer by a molecular layer deposition method (MLD).

[0044] Further, in step S4, a second inorganic layer is prepared by an atomic layer deposition method (ALD) using water vapor (H2O) and trimethylaluminum (TMA) gas.

[0045] Further, in step S4, the number of deposition cycles of the atomic layer deposition method (ALD) of the second inorganic layer is 5-200, and the thickness of the second inorganic layer is 0.5 nm-20 nm.

[0046] In a third aspect, the application further provides a liquid secondary battery, comprising: the negative electrode sheet of the secondary battery as described above, a positive electrode sheet, a separator, and an electrolyte.

[0047] In a fourth aspect, the application further provides a semi-solid secondary battery, comprising: the negative electrode sheet of the secondary battery as described above, a positive electrode sheet, and a semi-solid electrolyte between the positive and negative electrodes.

[0048] In a fifth aspect, the application further provides a solid-state secondary battery, comprising: the negative electrode sheet of the secondary battery as described above, a positive electrode sheet, and a solid-state electrolyte between the positive and negative electrodes.

[0049] Further, the negative electrode active material of the negative electrode active material layer comprises graphite.

[0050] Further, the negative electrode active material of the negative electrode active material layer comprises a silicon-carbon composite or a silicon-oxygen-carbon material composite.

[0051] Further, the negative electrode active material of the negative electrode active material layer comprises silicon.

[0052] Further, the negative electrode active material of the negative electrode active material layer is lithium metal.

[0053] Further, the positive electrode active material used by the positive electrode sheet comprises one of the following compounds: a lithium-containing compound, a sodium-containing compound.

[0054] The application has the following beneficial effects: Compared with the prior art, the application provides a solid composite film layer technology combining atomic layer deposition (ALD) and molecular layer deposition (MLD). The solid composite film layer at least comprises a first inorganic layer, a polymer layer and a second inorganic layer, and a strong connection is formed between the layers and between the first inorganic layer and the negative active material layer by chemical bonds, realizing the ordered mixing of organic components and inorganic components at the atomic and molecular levels, forming an organic-inorganic mixed multilayer artificial SEI film layer, which has good ion conductivity and electronic insulation capacity, is uniform and dense, and has adjustable thickness, thereby having less influence on the internal resistance of the secondary battery, realizing the close combination with the negative active material of the negative active material layer through chemical bonds, and having higher thermal stability and mechanical stability. The cycle life, coulombic efficiency and safety performance of the secondary battery are improved. BRIEF DESCRIPTION OF DRAWINGS

[0055] FIG. 1 The schematic diagram of the solid composite film layer deposited on the surface of the negative active material layer is provided.

[0056] The meanings represented by the serial numbers in the figure are as follows: 1. negative active material layer, 2. active group, 3. first inorganic layer metal, 4. first monomer, 5. second monomer, 6. second inorganic layer metal. DETAILED DESCRIPTION

[0057] In order to make the purpose, technical scheme and advantages of the application clearer, the application will be further described in detail below in combination with the drawings and examples. It should be understood that the specific examples described herein are only used to explain the application and should not be used to limit the application.

[0058] Exemplary embodiments of the present disclosure will be described in greater detail below with reference to the accompanying drawings. Although exemplary embodiments of the present disclosure are shown in the drawings, it should be understood that the present disclosure can be implemented in various forms and should not be limited by the embodiments set forth herein. Rather, these embodiments are provided so that the present disclosure can be more thoroughly understood and the scope of the present disclosure can be accurately conveyed to those skilled in the art.

[0059] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of a particular range. The range defined in this way is inclusive of the end values, and can be arbitrarily combined, i.e. any lower limit can be combined with any upper limit to form a range.

[0060] An embodiment of the present application provides a negative electrode tab of a secondary battery, a solid composite film layer is deposited on the surface of a negative electrode active material layer 1, the solid composite film layer comprises a first inorganic layer, a polymer layer and a second inorganic layer, and the layers of the solid composite film layer are connected by chemical bonds. Since the chemical bonds have extremely strong binding force, the solid composite film layer and the negative electrode active material layer 1 are firmly combined, and the layers of the solid composite film layer are firmly combined.

[0061] Compared with a naturally formed solid electrolyte interface film (SEI film), the solid composite film layer and the negative electrode active material layer 1 are firmly combined by chemical bonds, which has a significant advantage. During the charging and discharging process of the battery, the naturally formed SEI film is easy to break due to the mechanical stress caused by the volume change of the negative electrode active material, and a large amount of active lithium ions are consumed when a new SEI film is regenerated, which leads to the decrease of the coulomb efficiency and the capacity attenuation of the battery. The solid composite film layer of the present application is firmly combined with the negative electrode active material layer 1 by chemical bonds, which significantly improves the mechanical strength and stability of the interface, effectively resists the volume expansion of the negative electrode active material, and further reduces the consumption of active lithium ions.

[0062] At the same time, the uniform structure and chemical bond connection of the solid composite film layer make the ion transport path more optimized, and the interface impedance is significantly reduced, thereby improving the rate performance of the battery. Among them, by accurately controlling the thickness of the polymer layer, the channel of lithium ion migration is regulated, and higher ionic conductivity is obtained. In addition, the first inorganic layer and the second inorganic layer in the solid composite film layer have excellent thermal stability, which can maintain integrity in high temperature environment, avoid side reactions caused by failure of the solid composite film layer, and improve the safety of the battery. Compared with the naturally formed SEI film, the solid composite film layer can better isolate the direct contact between the electrolyte and the negative electrode active material, inhibit the occurrence of side reactions, improve the utilization rate of the electrolyte, and improve the stability, life and safety of the secondary battery.

[0063] In one embodiment, the thickness of the first inorganic layer is 0.1 nm-80 nm. Specifically, the thickness of the first inorganic layer is 0.1 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, or any value within any two of the above ranges. In the present application, the first inorganic layer is deposited on the surface of the negative electrode active material layer 1 by atomic layer deposition (ALD). In actual production process, the thickness formed by each deposition is about 0.1 nm. Since the first inorganic layer is deposited at least once, the minimum thickness of the first inorganic layer is 0.1 nm. When the thickness of the first inorganic layer is greater than 80 nm, the lithium ion insertion and extraction on the negative electrode active material will be affected due to the excessive thickness of the first inorganic layer, which will lead to the incomplete or uneven insertion of lithium ions on the negative electrode active material.

[0064] In one embodiment, the thickness of the polymer layer is 0.4 nm to 100 nm. Specifically, the thickness of the polymer layer is 0.4 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, or any value within a range between any two of the above values. When the thickness of the polymer layer is less than 0.4 nm, the buffering effect of the polymer layer on the expansion and shrinkage of the negative active material is weakened, and the mechanical stress caused by the volume change of the negative active material cannot be effectively alleviated, increasing the risk of rupture and peeling of the solid composite film layer. When the thickness of the polymer layer is greater than 100 nm, the migration path of lithium ions is too long due to the excessive thickness of the polymer layer, resulting in a decrease in ionic conductivity and an increase in internal resistance. In addition, the charge transfer speed of lithium ions through the excessively thick polymer layer is limited, resulting in a decrease in the charging and discharging efficiency of the battery.

[0065] In one embodiment, the thickness of the second inorganic layer is 0.1 nm to 80 nm. Specifically, the thickness of the second inorganic layer is 0.1 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, or any value within a range between any two of the above values. Similar to the case of the first inorganic layer, in the present application, the second inorganic layer is deposited on the polymer layer by atomic layer deposition (ALD). In actual production, the thickness formed by each deposition is about 0.1 nm. Since the second inorganic layer is deposited at least once, the minimum thickness of the second inorganic layer is 0.1 nm. When the thickness of the second inorganic layer is greater than 80 nm, the migration path of lithium ions is excessively increased due to the excessive thickness of the second inorganic layer, resulting in an increase in the internal resistance of the battery.

[0066] Preferably, the thickness of the first inorganic layer is 0.5 nm to 20 nm, the thickness of the polymer layer is 2 nm to 60 nm, and the thickness of the second inorganic layer is 0.5 nm to 20 nm. By limiting the thickness of each layer within the above range, the comprehensive optimization of the solid composite film layer in terms of mechanical properties, ion transport properties, and thermal stability, etc. can be achieved. Specifically, within the thickness range of 0.5 nm to 20 nm, the first inorganic layer and the second inorganic layer can make the solid composite film layer have both compactness and flexibility, resist the volume change of the negative active material, and avoid the problems of prolonged lithium ion migration path and increased interface impedance due to excessive thickness of the film layer. By controlling the thickness of the polymer layer to be 2 nm to 60 nm, the expansion stress during the charging and discharging process of the negative active material can be effectively buffered, while maintaining excellent ion transport channels and improving the rate performance.

[0067] In one embodiment, the upper surface of the second inorganic layer further includes repeating units composed of polymer and inorganic layers, with 1-50 repeating units. Specifically, after the first inorganic layer, polymer layer, and second inorganic layer are sequentially deposited on the upper surface of the negative electrode active material layer 1, the polymer and inorganic layers are repeatedly deposited on the upper surface of the second inorganic layer.

[0068] In actual production, the number of repeating cells can be adjusted according to the specific electrochemical performance requirements of the secondary battery. Specifically, the number of repeating cells can be optimized based on factors such as the charge / discharge rate, cycle life, and operating temperature range of the secondary battery. Fewer repeating cells (e.g., 2) may be more suitable for applications with high requirements for fast charge / discharge, while more repeating cells (e.g., 30) are suitable for battery systems requiring higher protection performance, longer lifespan, and more stable operation. By precisely adjusting the number of repeating cells, cost and production efficiency can be optimized while maintaining the performance of the solid composite film, thereby providing customized solutions for different types of battery products.

[0069] In one embodiment, the first inorganic layer and / or the second inorganic layer comprises an oxide selected from the following metals: aluminum (Al), titanium (Ti), silicon (Si), tin (Sn), vanadium (V), zirconium (Zr), zinc (Zn), lithium (Li), sodium (Na), potassium (K), niobium (Nb), tungsten (W), molybdenum (Mo), or a combination thereof.

[0070] That is, such as FIG. 1 As shown, the first inorganic layer metal 3 includes one or more of aluminum (Al), titanium (Ti), silicon (Si), tin (Sn), vanadium (V), zirconium (Zr), zinc (Zn), lithium (Li), sodium (Na), potassium (K), niobium (Nb), tungsten (W), and molybdenum (Mo). The second inorganic layer metal 6 includes one or more of aluminum (Al), titanium (Ti), silicon (Si), tin (Sn), vanadium (V), zirconium (Zr), zinc (Zn), lithium (Li), sodium (Na), potassium (K), niobium (Nb), tungsten (W), and molybdenum (Mo). In one embodiment, the first inorganic layer and / or the second inorganic layer comprises one of the following oxides: aluminum oxide (Al2O3), titanium dioxide (TiO2), silicon dioxide (SiO2), tin dioxide (SnO2), vanadium pentoxide (V2O5), zirconium dioxide (ZrO2), zinc oxide (ZnO), lithium oxide (Li2O), lithium superoxide (LiO2), sodium oxide (Na2O), sodium superoxide (NaO2), potassium oxide (K2O), potassium superoxide (KO2), niobium pentoxide (Nb2O5), tungsten trioxide (WO3), and molybdenum trioxide (MoO3).

[0071] In the present application, the first inorganic layer and / or the second inorganic layer comprises one of the oxides of aluminum oxide (Al2O3), titanium dioxide (TiO2), silicon dioxide (SiO2), tin dioxide (SnO2), vanadium pentoxide (V2O5), zirconium dioxide (ZrO2), zinc oxide (ZnO), lithium oxide (Li2O), superoxide lithium (LiO2), sodium oxide (Na2O), superoxide sodium (NaO2), potassium oxide (K2O), superoxide potassium (KO2), niobium pentoxide (Nb2O5), tungsten trioxide (WO3), molybdenum trioxide (MoO3), which can form uniform lithium ion channels in the first inorganic layer and / or the second inorganic layer, so that the first inorganic layer and / or the second inorganic layer has high lithium ion conductivity, which helps to improve the conduction efficiency of lithium ions in the battery, thereby reducing the impedance of the battery. By introducing these oxide materials, the transmission path of lithium ions can be optimized, energy loss and heat generation during charging and discharging of the battery can be reduced, and the charging and discharging efficiency of the battery can be improved. During the charging and discharging process of the battery, the first inorganic layer and / or the second inorganic layer can improve the ion selectivity and stability of the film layer, reduce the resistance of lithium ions on the electrode surface or the interface of the film layer, and further reduce the internal resistance of the battery.

[0072] At the same time, the first inorganic layer and / or the second inorganic layer comprising the above-mentioned oxides has higher mechanical strength, so that the first inorganic layer and / or the second inorganic layer has significant structural stability and anti-deformation ability, which can effectively inhibit the stress generated by the volume expansion and contraction of the negative active material during the charging and discharging process. For negative active materials, especially high-capacity materials such as silicon and silicon-carbon composites, they usually undergo significant volume changes during the cycle process, and such expansion and contraction can cause cracks, peeling and structural damage on the surface of the solid composite film layer. The high rigidity and hardness of the oxide material enable the first inorganic layer and the second inorganic layer to provide firm protection for the solid composite film layer, reduce the volume change of the negative active material, and prevent the solid composite film layer from cracking or breaking when the negative active material expands. In addition, the high-temperature resistance and chemical stability of these oxides enable the first inorganic layer and / or the second inorganic layer to maintain high mechanical strength under high temperature and harsh environment, avoiding the damage of the solid composite film layer, thereby improving the cycle stability of the battery.

[0073] In one embodiment, the second inorganic layer comprises one of the following compounds: fluoride, oxide, carbide and nitride.

[0074] In one embodiment, the first inorganic layer and the second inorganic layer both comprise an aluminum oxide (Al 2O3 ) thin layer. The aluminum oxide (Al2O3) thin film has excellent chemical stability and mechanical strength, which can effectively enhance the mechanical stability of the solid composite film layer.

[0075] In one embodiment, the second inorganic layer comprises a thin layer of aluminum fluoride (AlF3). The thin layer of aluminum fluoride (AlF3) has strong chemical stability and can effectively isolate the electrolyte, preventing direct contact between the electrolyte and the polymer layer and reducing the occurrence of side reactions. In addition, the thin layer of aluminum fluoride (AlF3) has relatively high mechanical strength, which can enhance the hardness of the second inorganic layer and provide better protection. In particular, during the charging and discharging process of the battery, the negative active material will undergo volume changes, and the thin layer of aluminum fluoride can resist the stress caused by the expansion and contraction of the negative active material, further maintaining the integrity of the solid composite membrane layer.

[0076] It should be noted that when the second inorganic layer comprises a thin layer of aluminum fluoride (AlF3), the solid composite membrane layer in the present application only comprises the first inorganic layer, the polymer layer and the second inorganic layer. That is, the repeated unit composed of the polymer layer and the inorganic layer will not be deposited on the second inorganic layer.

[0077] In one embodiment, the polymer layer is formed by polymerization of monomers with multiple functional groups. These multifunctional monomers polymerize to form a highly cross-linked three-dimensional network structure. Each monomer molecule contains multiple functional groups (such as carboxyl, amino or alcohol groups, etc.), which not only provide chemical connection points with adjacent monomers during polymerization, but also interact with the first inorganic layer or the second inorganic layer to form stable links. In practical applications, by selecting appropriate functional group types and polymerization conditions, the flexibility, electrical conductivity and other physical and chemical properties of the polymer layer can be adjusted to meet the needs of different types of secondary batteries for electrochemical performance.

[0078] Further, the monomers are selected from the following monomers: terephthaloyl chloride, ethylene glycol, terephthalamide, terephthaldehyde, terephthalic acid, p-phenylenediamine, hydroquinone, p-chlorobenzene, p-dinitrobenzene, 2,4-dinitroaniline, 4-4'-diaminodiphenyl ether, 4-4'-dihydroxydiphenyl ether, 4-4'-dicarboxy diphenyl ether, 4-4'-dichlorodiphenyl ether, ethylenediamine, oxalic acid, glyoxal, 1,2-dichloroethane, malonyl chloride, pyromellitic dianhydride, and derivatives of the above substances.

[0079] That is, as FIG. 1The first monomer 4 includes terephthaloyl chloride, ethylene glycol, terephthalamide, terephthaldehyde, terephthalic acid, p-phenylenediamine, hydroquinone, p-chlorobenzene, p-dinitrobenzene, 2,4-dinitroaniline, 4-4'-diaminodiphenyl ether, 4-4'-dihydroxydiphenyl ether, 4-4'-dicarboxy diphenyl ether, 4-4'-dichlorodiphenyl ether, ethylenediamine, oxalic acid, glyoxal, 1,2-dichloroethane, malonyl chloride, pyromellitic dianhydride, and derivatives of the above substances. The second monomer 5 includes terephthaloyl chloride, ethylene glycol, terephthalamide, terephthaldehyde, terephthalic acid, p-phenylenediamine, hydroquinone, p-chlorobenzene, p-dinitrobenzene, 2,4-dinitroaniline, 4-4'-diaminodiphenyl ether, 4-4'-dihydroxydiphenyl ether, 4-4'-dicarboxy diphenyl ether, 4-4'-dichlorodiphenyl ether, ethylenediamine, oxalic acid, glyoxal, 1,2-dichloroethane, malonyl chloride, pyromellitic dianhydride, and derivatives of the above substances.

[0080] It should be noted that, in the implementation of the present application, there is no strict restriction on the type and arrangement of the monomers used in the polymer layer. Specifically, the monomers used can be one or more of the above-mentioned monomers, which can be selected according to actual needs. In addition, the arrangement of the monomers (such as linear arrangement or alternating arrangement) can also be optimized and adjusted according to the specific battery performance requirements. Therefore, the present application has great flexibility and adjustability in monomer selection and arrangement, which enables the performance of the polymer layer to be customized according to different application scenarios to meet the electrochemical performance requirements of different secondary batteries.

[0081] Specifically, in one of the embodiments, the monomers used are terephthaloyl chloride and ethylene glycol.

[0082] Specifically, in one of the embodiments, the monomers used are terephthaloyl chloride and p-phenylenediamine.

[0083] Specifically, in one of the embodiments, the monomers used are ethylene glycol and p-phenylenediamine.

[0084] Specifically, in one of the embodiments, the monomers used are terephthaloyl chloride, ethylene glycol, and p-phenylenediamine.

[0085] In one of the embodiments, the active group 2 is formed on the surface of the negative active material layer 1, and the active group 2 is chemically bonded to the first inorganic layer.

[0086] In the present application, the surface of the negative active material layer 1 is introduced with active groups 2 with high reactivity. These active groups 2 are usually molecules containing reactive functional groups, such as hydroxyl (-OH), carboxyl (-COOH), amino (-NH2), etc., which are conducive to chemical reaction with the monomers of the first inorganic layer. These active groups 2 form stable chemical bonds, such as covalent bonds or coordination bonds, with the surface atoms of the first inorganic layer, thereby enhancing the binding force between the negative active material layer 1 and the first inorganic layer. In this way, the binding between the surface of the negative active material layer 1 and the solid composite film layer becomes more firm, greatly improving the adhesion and overall stability of the solid composite film layer.

[0087] Further, the active groups 2 include one of the following groups: hydroxyl (-OH), carboxyl (-COOH), amino (-NH2), aldehyde (-CHO), and nitro (-NO2).

[0088] Preferably, the active groups 2 are hydroxyl (-OH). Hydroxyl (-OH) has strong polarity and can form coordination bonds with metal ions of the first inorganic layer. In the present application, by introducing hydroxyl (-OH) on the surface of the negative active material layer 1, the adhesion between the negative active material layer 1 and the first inorganic layer is improved, the structural stability of the solid composite film layer during battery charging and discharging is enhanced, and the possibility of peeling and falling off of the solid composite film layer is reduced.

[0089] In one embodiment, the negative active material layer 1 includes one of the following negative active materials: graphite, hard carbon, silicon-carbon composite, silicon-oxygen-carbon material composite, silicon, lithium metal, lithium titanium oxide, silicon-based alloy, tin-based alloy, lithium-based alloy (such as lithium-silver alloy), copper or copper-based alloy, or a combination thereof.

[0090] In one embodiment, the negative active material layer 1 uses a negative active material including graphite. Graphite as a negative active material has good electrical conductivity, chemical stability, and low swelling, so it can maintain a relatively stable structure during battery charging and discharging, thereby effectively improving the cycle life and safety of the battery.

[0091] In one embodiment, the negative active material layer 1 uses a negative active material including silicon-carbon composite or silicon-oxygen-carbon material composite. Silicon-carbon composite takes advantage of the high specific capacity of silicon, and through the composite with carbon material, effectively inhibits the problem of volume expansion of silicon during charging and discharging, thereby improving the cycle stability and mechanical strength of the battery. The silicon-oxygen-carbon material composite combines the characteristics of silicon, oxygen, and carbon material, not only can provide higher specific capacity, but also can further improve the stability of the negative active material, effectively enhance the durability and safety of the negative active material.

[0092] In one embodiment, the negative active material used in the negative active material layer 1 includes silicon. Silicon has a very high theoretical specific capacity (about 3579 mAh / g) as a negative active material, much higher than traditional graphite materials, which can significantly improve the energy density of the secondary battery.

[0093] In one embodiment, the negative active material used in the negative active material layer 1 is lithium metal.

[0094] In a second aspect, the present application also provides a method for preparing a negative electrode sheet of a secondary battery, the negative electrode sheet comprising a negative active material layer 1, and a solid composite film layer deposited on the surface of the negative active material layer 1 by the following steps: S1. introducing active groups 2 on the surface of the negative active material layer 1 by chemical treatment; S2. forming a first inorganic layer on the active groups 2 by atomic layer deposition; S3. forming a polymer layer on the upper surface of the first inorganic layer by molecular layer deposition; and S4. forming a second inorganic layer on the upper surface of the polymer layer by atomic layer deposition.

[0095] In step S1, active groups 2 are introduced on the surface of the negative active material layer 1 by modifying the surface of the negative active material layer 1. These active groups 2 can increase the reactivity of the surface of the negative active material layer 1, providing attachment sites for the subsequent deposition of the first inorganic layer, so that the negative active material layer 1 can better combine with the subsequently deposited first inorganic layer.

[0096] In step S2, the atomic layer deposition (ALD) method is used to form a first inorganic layer on the surface of the active groups 2. The atomic layer deposition method can more accurately control the thickness and composition of the first inorganic layer by layer-by-layer deposition, ensuring that the first inorganic layer forms a uniform film on the surface of the negative active material layer 1. The first inorganic layer enhances the structural strength of the solid composite film layer and provides a stable substrate for the deposition of subsequent layers.

[0097] In step S3, the molecular layer deposition (MLD) method is used to deposit a polymer layer on the first inorganic layer. This process can form a strong chemical bond between the polymer layer and the first inorganic layer, ensuring the stability and integrity of the entire film layer. The polymer layer has good flexibility, making the solid composite film layer have stronger resistance to mechanical stress. Specifically, during the charging and discharging process of the battery, the negative active material will undergo expansion and contraction, and the flexibility of the polymer layer can effectively relieve the stress caused by this volume change, preventing the solid composite film layer from cracking or falling off.

[0098] In step S4, a second inorganic layer is deposited on the upper surface of the polymer layer using an atomic layer deposition method (ALD). The second inorganic layer not only further enhances the mechanical strength and electrochemical stability of the solid composite film layer, but also provides additional protection for the polymer layer, avoiding the reaction of the electrolyte with the polymer layer.

[0099] In one embodiment, in step S1, the active groups 2 introduced by the chemical treatment on the surface of the negative active material layer 1 are selected from one of the following groups: hydroxyl (-OH), carboxyl (-COOH), amino (-NH2), aldehyde (-CHO) and nitro (-NO2).

[0100] Further, in step S1, the chemical treatment is a micro-oxidation treatment on the surface of the negative active material layer 1 to introduce hydroxyl (-OH) active groups 2. In step S1, the hydroxyl (-OH) is introduced on the surface of the negative active material layer 1 by micro-oxidation treatment. The hydroxyl (-OH) has strong polarity and can form a coordination bond with the metal ions of the first inorganic layer, improving the adhesion between the negative active material layer 1 and the first inorganic layer and enhancing the structural stability of the solid composite film layer during the charging and discharging process of the battery.

[0101] In one embodiment, in step S1, the micro-oxidation treatment method is a plasma oxidation method. The plasma oxidation method generates active groups 2, such as hydroxyl (-OH), on the surface of the negative active material layer 1 by using high-energy plasma, which can uniformly and accurately control the degree of oxidation on the surface of the negative active material layer 1. In addition, the plasma oxidation method has the characteristics of low-temperature treatment and strong controllability, which can avoid the risk of structural damage to the negative active material caused by high temperature.

[0102] In one embodiment, in step S1, the micro-oxidation treatment method is an oxidant oxidation method, and the oxidant used is hydrogen peroxide solution.

[0103] Hydrogen peroxide solution as an oxidant has strong oxidizing properties and can effectively introduce oxidizing functional groups at lower temperatures, significantly improving the chemical reactivity of the surface of the negative active material layer 1. Compared with traditional high-temperature oxidation methods, hydrogen peroxide oxidation method can avoid thermal damage to the structure of the negative active material. Secondly, the oxidant oxidation method is simple to operate and has lower cost, with good economic benefits. In addition, hydrogen peroxide solution does not produce harmful by-products during oxidation, which has good environmental friendliness.

[0104] In one embodiment, the first inorganic layer is prepared by atomic layer deposition (ALD) using water vapor (H2O) and trimethylaluminum (TMA) gas in step S2. In this embodiment, water vapor (H2O) reacts with trimethylaluminum (TMA) to form an aluminum oxide (Al2O3) thin layer, which is the first inorganic layer. The aluminum oxide (Al2O3) thin layer has excellent chemical stability and mechanical strength, which can effectively enhance the mechanical stability of the solid composite membrane layer. Water vapor (H2O) as one of the reaction precursors has the advantages of low cost, environmental friendliness and easy availability, while the high reactivity of trimethylaluminum (TMA) improves the deposition rate of the aluminum oxide (Al2O3) thin layer and improves production efficiency. In addition, atomic layer deposition (ALD) can achieve atomic layer control to ensure the quality of the aluminum oxide (Al2O3) thin layer and improve the stability of the solid composite membrane layer.

[0105] Further, in step S2, the deposition cycle number of the atomic layer deposition (ALD) of the first inorganic layer is 1-800 times, and the thickness of the first inorganic layer is 0.1 nm-80 nm.

[0106] Further, in step S2, the deposition cycle number of the atomic layer deposition (ALD) of the first inorganic layer is 5-200 times, and the thickness of the first inorganic layer is 0.5 nm-20 nm.

[0107] In actual production, the thickness of the first inorganic layer formed by atomic layer deposition (ALD) is about 0.1 nm each time. When the deposition cycle number of atomic layer deposition (ALD) is 1-800 times, the thickness of the first inorganic layer is about 0.1 nm-80 nm; when the deposition cycle number of atomic layer deposition (ALD) is 5-200 times, the thickness of the first inorganic layer is about 0.5 nm-20 nm.

[0108] In one embodiment, the polymer layer is prepared by molecular layer deposition (MLD) using a monomer with multiple functional groups in step S3; the monomer is selected from the following monomers: terephthaloyl chloride, ethylene glycol, terephthalamide, terephthaldehyde, terephthalic acid, p-phenylenediamine, hydroquinone, p-chlorobenzene, p-dinitrobenzene, 2,4-dinitroaniline, 4-4'-diaminodiphenyl ether, 4-4'-dihydroxydiphenyl ether, 4-4'-dicarboxy diphenyl ether, 4-4'-dichlorodiphenyl ether, ethylenediamine, oxalic acid, glyoxal, 1,2-dichloroethane, malonyl chloride, pyromellitic dianhydride, and derivatives of the above substances.

[0109] In one embodiment, the monomers used in step S3 are terephthaloyl chloride and ethylene glycol, which are polymerized into a polyethylene terephthalate thin layer by molecular layer deposition (MLD). In this embodiment, terephthaloyl chloride has high reactivity and can rapidly react with the hydroxyl groups of ethylene glycol to form stable ester bonds. The hydroxyl groups at both ends of ethylene glycol help to form long-chain polymers, providing better flexibility and chemical stability. By molecular layer deposition (MLD), the thickness of the polyethylene terephthalate thin layer can be effectively controlled, and the uniformity and density of the polyethylene terephthalate thin layer can be ensured. The polyethylene terephthalate thin layer can improve the flexibility of the solid composite film layer to adapt to the expansion and contraction of the negative active material volume during the charging and discharging process of the battery.

[0110] Further, in step S3, the number of deposition cycles of the polymer layer by molecular layer deposition (MLD) is 1-250, and the thickness of the polymer layer is 0.4 nm-100 nm.

[0111] Further, in step S3, the number of deposition cycles of the polymer layer by molecular layer deposition (MLD) is 5-150, and the thickness of the polymer layer is 2 nm-60 nm.

[0112] In actual production, the thickness of the polymer layer formed by each deposition of molecular layer deposition (MLD) is about 0.5 nm. When the number of deposition cycles of molecular layer deposition (MLD) is 1-250, the thickness of the polymer layer is about 0.5 nm-100 nm; when the number of deposition cycles of molecular layer deposition (MLD) is 5-150, the thickness of the polymer layer is about 2 nm-60 nm.

[0113] In one embodiment, the monomers used in step S3 are terephthaloyl chloride and ethylene glycol, which are polymerized into a polyethylene terephthalate thin layer by molecular layer deposition (MLD). In this embodiment, terephthaloyl chloride has high reactivity and can rapidly react with the hydroxyl groups of ethylene glycol to form stable ester bonds. The hydroxyl groups at both ends of ethylene glycol help to form long-chain polymers, providing better flexibility and chemical stability. By molecular layer deposition (MLD), the thickness of the polyethylene terephthalate thin layer can be effectively controlled, and the uniformity and density of the polyethylene terephthalate thin layer can be ensured. The polyethylene terephthalate thin layer can improve the flexibility of the solid composite film layer to adapt to the expansion and contraction of the negative active material volume during the charging and discharging process of the battery.

[0114] In one embodiment, the monomers used are ethylene glycol and p-phenylenediamine, which are polymerized into a poly(p-phenylene glycol amide) thin layer by molecular layer deposition (MLD).

[0115] In one embodiment, the monomers used are terephthaloyl chloride, ethylene glycol, and p-phenylenediamine, which are polymerized into a poly(p-phenylene glycol amide) thin layer by molecular layer deposition (MLD).

[0116] In one of the embodiments, in step S4, the second inorganic layer is prepared by atomic layer deposition (ALD) using water vapor (H2O) and trimethylaluminum (TMA) gas. In this embodiment, water vapor (H2O) reacts with trimethylaluminum (TMA) to form an aluminum oxide (Al2O3) thin layer, which is the second inorganic layer. The aluminum oxide (Al2O3) thin layer not only further enhances the mechanical strength and electrochemical stability of the solid composite film layer, but also provides additional protection for the polymer layer, avoiding the reaction of the electrolyte with the polymer layer.

[0117] Further, in step S4, the number of deposition cycles of the atomic layer deposition (ALD) of the second inorganic layer is 5-200, and the thickness of the second inorganic layer is 0.5 nm-20 nm.

[0118] In actual production, the thickness of the second inorganic layer formed by atomic layer deposition (ALD) is about 0.1 nm each time. When the number of deposition cycles of the atomic layer deposition (ALD) is 5-200, the thickness of the second inorganic layer is about 0.5 nm-20 nm.

[0119] In a third aspect, the present application also provides a liquid secondary battery, comprising: the negative electrode sheet, the positive electrode sheet, the separator and the electrolyte of the above-mentioned secondary battery. The surface of the negative electrode active material layer 1 of the negative electrode sheet of the liquid secondary battery is deposited with a solid composite film layer, which is formed by sequentially depositing a first inorganic layer, a polymer layer and a second inorganic layer, thereby improving the uniformity of the solid composite film layer, and at the same time, the solid composite film layer has higher mechanical stability and flexibility to withstand the volume expansion and contraction of the negative electrode active material during the charging and discharging process of the battery, preventing the rupture or shedding of the solid composite film layer, and improving the electrochemical performance of the battery.

[0120] In a fourth aspect, the present application also provides a semi-solid secondary battery, comprising: the negative electrode sheet, the positive electrode sheet and the semi-solid electrolyte between the positive and negative electrodes of the above-mentioned secondary battery.

[0121] In a fifth aspect, the present application also provides a solid-state secondary battery, comprising: the negative electrode sheet, the positive electrode sheet and the solid-state electrolyte between the positive and negative electrodes of the above-mentioned secondary battery.

[0122] In one of the embodiments, the negative electrode active material of the negative electrode active material layer 1 comprises graphite.

[0123] In one of the embodiments, the negative electrode active material of the negative electrode active material layer 1 comprises silicon-carbon composite or silicon-oxygen-carbon material composite.

[0124] In one of the embodiments, the negative electrode active material of the negative electrode active material layer 1 comprises silicon.

[0125] In one embodiment, the negative active material of the negative active material layer 1 is lithium metal.

[0126] In one embodiment, the positive active material used by the positive electrode sheet includes one of the following compounds: a lithium-containing compound, a sodium-containing compound. Specifically, the lithium-containing compound includes one of the following compounds: lithium iron phosphate, lithium manganese iron phosphate, lithium cobaltate, lithium manganate, lithium nickel cobalt manganate, lithium nickel cobalt aluminate, lithium-rich lithium nickel cobalt manganate. The sodium-containing compound includes one of the following compounds: sodium iron phosphate, sodium pyrophosphate, sodium pyrophosphate, sodium vanadium phosphate, sodium vanadium fluoride phosphate, sodium iron sulfate, sodium copper iron manganate, sodium iron nickel manganate, sodium hexacyanoferrate, sodium hexacyanoferrate. Further, in this embodiment, the secondary battery prepared by the positive electrode sheet is a lithium ion battery or a sodium ion battery.

[0127] The application will be further described in detail below in conjunction with examples and comparative examples: Hereinafter, the embodiments of the present application will be described. The facts described below are exemplary and are only used to explain the present application and cannot be understood as a limitation of the present application. If a specific technique or condition is not specified in the embodiments, it is performed according to the technique or condition described in the literature in the art or according to the product manual. If the reagent or instrument used is not specified by the manufacturer, it is a conventional product that can be obtained by purchase.

[0128] One, secondary battery Example 101: (1) Preparation of the negative electrode sheet: Preparation of the negative electrode sheet: Graphite was selected as the negative active material, and the graphite was mixed with a conductive agent and a binder to prepare a negative electrode slurry. The negative electrode slurry was uniformly coated on the copper foil negative current collector, and then dried. The dried electrode sheet was compacted and sliced to obtain a pre-prepared negative electrode sheet.

[0129] ① The first inorganic layer of aluminum oxide was deposited on the surface of the graphite by atomic layer deposition (ALD).

[0130] 1) Preparation of the pre-prepared negative electrode sheet: The surface of the pre-prepared negative electrode sheet was cleaned to remove surface dirt and impurities. After thorough cleaning with ultrasonic waves, the pre-prepared negative electrode sheet was dried in an oven at a temperature of 100°C for 30 min; Surface activation: the pre-prepared negative electrode sheet was treated with hydrogen peroxide (25% by mass) to generate hydroxyl active groups 2 on the surface of the graphite, and then dried at 100°C.

[0131] 2) Preparation of the ALD reaction furnace: Put the dried pre-prepared negative electrode sheet into the ALD reaction furnace, and the temperature in the furnace is 150°C; Reaction gas: trimethylaluminum pulse gas and water vapor.

[0132] 3) Deposition of aluminum oxide: Pass in trimethylaluminum pulse gas as the aluminum source, and trimethylaluminum reacts with the hydroxyl groups on the surface of graphite to form Gr-O-Al-CH4- (CH3)2 and methane; The trimethylaluminum pulse time is 1s, and the gas partial pressure of trimethylaluminum is 20mTorr; Use nitrogen or argon to clean the reaction furnace to remove methane and unreacted trimethylaluminum pulse gas; Pass in pulse water vapor as the oxygen source, and water vapor continues to react with Gr-O-Al-CH4- (CH3)2 to form Al-OH, and then form aluminum oxide; The water vapor pulse time is 1s, and the gas partial pressure of water vapor is 20mTorr; Use nitrogen or argon to clean the reaction furnace to remove hydrogen and unreacted water vapor.

[0133] 4) Cycle deposition: The deposition reaction of trimethylaluminum gas and water vapor is cycled, and each ALD cycle deposits an aluminum oxide layer with a thickness of about 0.1nm. After 100 cycles, an aluminum oxide thin layer with a thickness of 10nm is obtained, which is the first inorganic layer in this embodiment.

[0134] 5) Cleaning and drying: After completing the deposition cycle, take out the pre-prepared negative electrode sheet, and use nitrogen or argon to clean the reaction furnace to remove residual reaction gas; Then put the pre-prepared negative electrode sheet into the oven and dry at 100°C.

[0135] At this point, the deposition of the aluminum oxide thin layer on the surface of graphite is achieved, and the first inorganic layer is obtained.

[0136] ②Deposition of a polymer layer on the aluminum oxide thin layer of the first inorganic layer by molecular layer deposition (MLD).

[0137] 1) Put the pre-prepared negative electrode sheet with the deposited aluminum oxide thin layer into the MLD reaction furnace.

[0138] 2) MLD reaction condition settings: Temperature: Set the reaction chamber temperature to 85°C; Reaction gas: terephthaloyl chloride and ethylene glycol (EG).

[0139] 3) MLD reaction steps: a. Pass in terephthaloyl chloride pulse gas: The terephthaloyl chloride gas is introduced into the reaction chamber. The terephthaloyl chloride reacts with the hydroxyl groups on the surface of the aluminum oxide thin layer to form an ester (Al-O-CO-C6H4-CO-Cl) and release hydrogen chloride; The pulse time of the terephthaloyl chloride is 0.1 s, and the gas partial pressure of the terephthaloyl chloride is 10 mTorr; The reaction chamber is purged with nitrogen or argon to remove the residual terephthaloyl chloride gas and hydrogen chloride.

[0140] b. Introduce an ethylene glycol pulse gas: The ethylene glycol gas is introduced into the reaction chamber, and the -OH groups of the ethylene glycol react with the ester (Al-O-CO-C6H4-CO-Cl) to form Al-O-C6H4-CO-O-C2H4-OH; The pulse time of the ethylene glycol is 0.1 s, and the gas partial pressure of the ethylene glycol is 10 mTorr; The reaction chamber is purged with nitrogen or argon to remove the residual ethylene glycol gas; c. Cycle deposition: The reaction cycle of terephthaloyl chloride and ethylene glycol is repeated, and each MLD cycle deposits a polyethylene terephthalate thin layer with a thickness of about 0.4 nm. After 100 cycles, a polyethylene terephthalate thin layer with a thickness of 40 nm is obtained, which is the polymer layer in this embodiment.

[0141] d. Purification and drying: The reaction chamber is purged with nitrogen or argon to remove the ethylene glycol; After the deposition cycle is completed, the pre-prepared negative electrode sheet is removed, and the reaction furnace is purged with nitrogen or argon to remove the residual reaction gas; The pre-prepared negative electrode sheet is dried in an oven at 100°C.

[0142] At this point, the deposition of the polyethylene terephthalate thin layer on the aluminum oxide thin layer is achieved, and the polymer layer is obtained.

[0143] ③ A second inorganic layer is deposited on the polyethylene terephthalate thin layer of the polymer layer by atomic layer deposition (ALD).

[0144] 1) The pre-prepared negative electrode sheet with the deposited polyethylene terephthalate thin layer is placed in the ALD reaction chamber.

[0145] 2) ALD reaction chamber preparation: The dried pre-prepared negative electrode sheet is placed in the ALD reaction furnace, and the furnace temperature is 150°C; Reaction gas: trimethylaluminum pulse gas and water vapor.

[0146] 3) Deposition of aluminum oxide: The pulse gas of trimethylaluminum is introduced as the aluminum source, and trimethylaluminum reacts with the hydroxyl group on the surface of the polyethylene terephthalate thin layer to form Gr-O-Al-CH4-(CH3)2 and methane; The pulse time of trimethylaluminum is 1 s, and the gas partial pressure of trimethylaluminum is 20 mTorr; The reaction furnace is cleaned with nitrogen or argon to remove methane and unreacted trimethylaluminum; The pulse gas of water vapor is introduced as the oxygen source, and water vapor continues to react with Gr-O-Al-CH4-(CH3)2 to form Al-OH, and then form aluminum oxide; The pulse time of water vapor is 1 s, and the gas partial pressure of water vapor is 20 mTorr.

[0147] The reaction furnace is cleaned with nitrogen or argon to remove hydrogen and unreacted water vapor.

[0148] 4) Cyclic deposition: The deposition reaction of trimethylaluminum gas and water vapor is carried out cyclically, and each ALD cycle deposits an aluminum oxide layer with a thickness of about 0.1 nm. After 100 cycles, an aluminum oxide thin layer with a thickness of 10 nm is obtained, which is the second inorganic layer in this embodiment.

[0149] 5) Cleaning and drying: After the deposition cycle is completed, the pre-prepared negative electrode sheet is taken out, and the reaction furnace is cleaned with nitrogen or argon to remove residual reaction gas.

[0150] Then the pre-prepared negative electrode sheet is dried at 100°C.

[0151] At this point, the deposition of the aluminum oxide thin layer on the surface of the polyethylene terephthalate thin layer is realized, and the second inorganic layer is obtained. At the same time, the preparation of the negative electrode sheet is realized. The surface of the negative electrode active material layer 1 of the negative electrode sheet is deposited with a solid composite film layer. For details, see FIG. 1 .

[0152] (2) Preparation of positive electrode sheet: The positive electrode active material lithium iron phosphate LiFePO4 (LFP), conductive carbon black (SP), and binder polyvinylidene fluoride (PVDF) are mixed uniformly in a mass ratio of 95:2:3 with N-methyl pyrrolidone, and then coated on the carbon-coated aluminum foil. After drying, cold pressing, slitting, sheet making, welding tabs, and gluing, a positive electrode sheet is prepared.

[0153] (3) Preparation of separator: A polyethylene (PE) / ceramic separator is selected as the separator, and is cut to the size corresponding to the battery.

[0154] (4) Preparation of secondary battery: The positive electrode sheet, the separator and the negative electrode sheet are sequentially stacked in order to form a battery cell structure, ensuring that the separator completely covers the positive and negative electrodes to avoid short circuit; the stacked battery cell is placed in an aluminum plastic film for packaging and sealed by hot pressing; after baking, the prepared electrolyte is injected into the packaged battery, and the battery is sealed again by hot sealing to ensure the sealing of the secondary battery; the battery after injection is subjected to processes such as soaking, formation, aging and capacity distribution to obtain a battery to be tested.

[0155] Examples 102-103: Examples 102-103 are used to illustrate a secondary battery disclosed in the present application, which includes most of the operations of Example 101 in Table 1, the main difference being that the thickness of the first inorganic layer introduced in the negative active material layer 1 of the secondary battery in Examples 102-103 is 5 nm and 20 nm, respectively, and the specific parameters are as described in the data of each corresponding example in Table 1.

[0156] Examples 104-105: Examples 104-105 are used to illustrate a secondary battery disclosed in the present application, which includes most of the operations of Example 101 in Table 1, the main difference being that the thickness of the second inorganic layer introduced in the negative active material layer 1 of the secondary battery in Examples 104-105 is 5 nm and 20 nm, respectively, and the specific parameters are as described in the data of each corresponding example in Table 1.

[0157] Example 106: Example 106 is used to illustrate a secondary battery disclosed in the present application, which includes most of the operations of Example 101 in Table 1, the main difference being that the active group 2 introduced in the negative active material layer 1 of the secondary battery in Example 106 is a carboxyl group (-COOH), and the specific parameters are as described in the data of each corresponding example in Table 1.

[0158] Example 107: Example 107 is used to illustrate a secondary battery disclosed in the present application, which includes most of the operations of Example 101 in Table 1, the main difference being that the second inorganic layer introduced in the negative active material layer 1 of the secondary battery in Example 107 is an aluminum fluoride thin layer, and the specific parameters are as described in the data of each corresponding example in Table 1.

[0159] Example 108: Example 108 is used to illustrate a secondary battery disclosed in the present application, which includes most of the operations of Example 101 in Table 1, the main difference being that the monomer used for introducing a polymer layer on the negative active material layer 1 of the secondary battery in Example 108 is terephthaloyl chloride and p-phenylenediamine, and the specific parameters are as described in the data of each corresponding example in Table 1.

[0160] Example 109: Example 109 is used to illustrate a secondary battery disclosed in the present application, comprising most of the operations of Example 101 in Table 1, the main difference is that the monomers used in the polymer layer introduced on the negative electrode active material layer 1 of the secondary battery in Example 109 are ethylene glycol and p-phenylenediamine, and the specific parameters are as described in the data of each corresponding example in Table 1.

[0161] Example 110: Example 110 is used to illustrate a secondary battery disclosed in the present application, comprising most of the operations of Example 101 in Table 1, the main difference is that the monomers used in the polymer layer introduced on the negative electrode active material layer 1 of the secondary battery in Example 110 are terephthaloyl chloride, ethylene glycol and p-phenylenediamine, and the specific parameters are as described in the data of each corresponding example in Table 1.

[0162] Examples 111-112: Examples 111-112 are used to illustrate a secondary battery disclosed in the present application, comprising most of the operations of Example 101 in Table 1, the main difference is that the thickness of the polymer layer introduced on the negative electrode active material layer 1 of the secondary battery in Examples 111-112 is 4 nm and 60 nm respectively, and the specific parameters are as described in the data of each corresponding example in Table 1.

[0163] Example 113: Example 113 is used to illustrate a secondary battery disclosed in the present application, comprising most of the operations of Example 101 in Table 1, the main difference is that the negative electrode active material used in the secondary battery in Example 113 is a silicon-carbon composite, and the specific parameters are as described in the data of each corresponding example in Table 1.

[0164] Example 114: Example 114 is used to illustrate a secondary battery disclosed in the present application, comprising most of the operations of Example 101 in Table 1, the main difference is that the negative electrode active material used in the secondary battery in Example 114 is silicon, and the specific parameters are as described in the data of each corresponding example in Table 1.

[0165] Comparative Examples 1001-1003: Comparative Examples 1001-1003 are used to illustrate a secondary battery disclosed in the present application, comprising most of the operations of Example 101 in Table 1, the main difference is that the upper surface of the negative electrode active material of the secondary battery in Comparative Examples 1001-1003 is not artificially treated, and the specific parameters are as described in the data of each corresponding example in Table 1.

[0166] Comparative Example 1004: Comparative Example 1004 was used to illustrate a secondary battery according to the present disclosure, and included most of the operations of Example 101 in Table 1, except that only the first inorganic layer was introduced on the negative active material layer 1 of the secondary battery in Comparative Example 1004, and the specific parameters were as described in Table 1 for each comparative example.

[0167] Comparative Example 1005: Comparative Example 1005 was used to illustrate a secondary battery according to the present disclosure, and included most of the operations of Example 101 in Table 1, except that only the first inorganic layer and the polymer layer were introduced on the negative active material layer 1 of the secondary battery in Comparative Example 1005, and the specific parameters were as described in Table 1 for each comparative example.

[0168] II. Performance test of the secondary battery prepared above (1) DC internal resistance Adjust 50% SOC: 25±2℃, charge the secondary battery to 3.65V at a constant current of 0.5C, then convert to constant voltage charging, the cutoff condition is that the current is less than 0.05C, after charging, stand for 10min, then discharge to 50% SOC at a constant current of 0.5C; DC resistance test: stand for 60min, record the end voltage V1, then discharge for 30s at a current of 2C (2.4A), record the end voltage V2; DC internal resistance: (V1-V2) / 2.4*1000, recorded as the measured DC internal resistance value.

[0169] The test results of the DC internal resistance are shown in Table 2.

[0170] (2) Rate performance (2C discharge ratio) Charging: 25±2℃, charge the secondary battery to 3.65V at a constant current of 0.5C, then convert to constant voltage charging, the cutoff condition is that the current is less than 0.05C; Standing: 25±2℃, stand for 10min after charging; Discharging: 25±2℃, discharge to 2.5V at a constant current of 0.5C, record the discharge capacity as C0; Standing: 25±2℃, stand for 10min after discharging; Charging: 25±2℃, charge the secondary battery to 3.65V at a constant current of 0.5C, then convert to constant voltage charging, the cutoff condition is that the current is less than 0.05C Standing: 25±2℃, stand for 10min after charging; Discharging: 25±2℃, discharge to 2.5V at a constant current of 2.0C, record the discharge capacity as C1; Discharge ratio: C1 / C0*100%, recorded as the 2C discharge ratio.

[0171] The test results of the rate performance are shown in Table 2.

[0172] (3) Capacity retention rate Charging: 25±2℃, the secondary battery was charged at a rate of 0.5C to 3.65V by constant current, and then converted to constant voltage charging, and the cut-off condition was that the current was less than 0.05C; Rest: 25±2℃, after the end of charging, rest for 10min; Discharging: 25±2℃, then discharged at a rate of 0.5C by constant current to 2.5V, and the discharge capacity was recorded as C'1; Rest: 25±2℃, after the end of discharging, rest for 10min; Cycling: repeat the above steps 1000 times, and record the discharge capacity of the 1000th cycle as C 1000 ; Capacity retention rate: C 1000 / C'1*100% is recorded as the capacity retention rate corresponding to 1000 cycles.

[0173] Note: The negative active material used in Example 114 and Comparative Example 1003 is silicon, and the number of times of secondary battery cycle charging and discharging in these two examples cannot reach 1000 times, but only 500 cycles. Therefore, for Example 114 and Comparative Example 1003, the capacity retention rate corresponding to 500 cycles of cycle charging and discharging is measured.

[0174] The test results of the capacity retention rate are shown in Table 2.

[0175] (4) Coulombic efficiency The coulombic efficiency is the ratio of the discharge capacity to the charge capacity corresponding to each single cycle during the cycle process C n 放电 / C n 充电 *100% of the 1000th cycle is recorded as the coulombic efficiency C 1000 放电 / C 1000 充电 *100%.

[0176] Note: In Table 1, thin layer A is a polyethylene terephthalate thin layer, thin layer B is a poly(p-phenylene terephthalamide) thin layer, thin layer C is a poly(p-phenylene glycol amide) thin layer, and thin layer D is a poly(p-phenylene glycol terephthalamide) thin layer.

[0177] Table 2 From the test results of Table 2, it can be seen that the secondary batteries of Examples 101-113 have relatively small DC internal resistance, which is distributed between 47.9 mΩ and 55.1 mΩ. The solid composite film layer (i.e., artificial SEI film) deposited on the negative active material layer 1 in the present application makes the ion conduction path in the secondary battery more stable. The solid composite film layer is chemically bonded between the negative active material layer 1 and each layer of the solid composite film layer, which enhances the ion conduction ability of each layer of the solid composite film layer and effectively reduces the DC internal resistance.

[0178] The DC internal resistance of Comparative Examples 1001-1003 is relatively large, which is distributed between 59.8 mΩ and 78.6 mΩ. The SEI film of the secondary batteries of Comparative Examples 1001-1003 is naturally formed. Due to the non-uniform structure and poor mechanical stability, the naturally formed SEI film will be broken or regenerated during the charging and discharging process of the secondary battery, which not only consumes active lithium ions to form more by-products, but also increases the thickness of the naturally formed SEI film and prolongs the migration path of lithium ions, thereby increasing the DC resistance in the secondary battery.

[0179] In Comparative Example 1004, only the first inorganic layer (aluminum oxide thin layer) is introduced on the negative active material layer 1 of the secondary battery. In this comparative example, although the aluminum oxide thin layer can inhibit the volume change of the negative active material to a certain extent, the single aluminum oxide thin layer cannot buffer the volume change of the negative active material, which leads to the breakage of the aluminum oxide thin layer due to fatigue, the contact of the electrolyte with the negative active material to form a new naturally formed SEI film, the consumption of active lithium ions, the prolongation of the migration path of lithium ions, and the increase of the DC internal resistance of the secondary battery.

[0180] In Comparative Example 1005, only the first inorganic layer (aluminum oxide thin layer) and the polymer layer (polyethylene terephthalate thin layer) are introduced on the negative active material layer 1 of the secondary battery. In this comparative example, although the aluminum oxide thin layer can inhibit the volume change of the negative active material to a certain extent and the polyethylene terephthalate thin layer has a certain buffering effect on the volume change of the negative active material. However, in this comparative example, the polyethylene terephthalate thin layer is in direct contact with the electrolyte and reacts with the electrolyte to consume active lithium ions, while a new naturally formed SEI film is formed on the surface of the polyethylene terephthalate thin layer, which prolongs the migration path of lithium ions and increases the DC internal resistance of the secondary battery.

[0181] As can be seen from the test results of Examples 101-103, when the thickness of the first inorganic layer of aluminum oxide thin layer is 5 nm, the internal resistance of the secondary battery exhibits a relatively low internal resistance (48.1 mΩ), and with the increase of the thickness of the first inorganic layer of aluminum oxide thin layer (e.g., the thickness of the first inorganic layer of aluminum oxide thin layer in Example 101 is 10 nm, and the thickness of the first inorganic layer of aluminum oxide thin layer in Example 103 is 20 nm), the internal resistance of the secondary battery shows a slightly increasing trend (e.g., the internal resistance of the first inorganic layer of aluminum oxide thin layer in Example 101 is 50.2 mΩ, and the internal resistance of the first inorganic layer of aluminum oxide thin layer in Example 103 is 51.2 mΩ). This is mainly because when the thickness of the first inorganic layer of aluminum oxide thin layer is small, the migration channel of lithium ions on the negative electrode active material layer 1 of the negative electrode sheet is not too obstructed, and the lithium ions can more easily migrate through the first inorganic layer of aluminum oxide thin layer, so that the secondary battery has a relatively low internal resistance. When the thickness of the first inorganic layer of aluminum oxide thin layer gradually increases, the migration path of lithium ions in the first inorganic layer of aluminum oxide thin layer gradually increases, and the resistance that needs to be overcome by lithium ion transmission gradually increases, thereby causing the internal resistance of the secondary battery to also show an increasing trend.

[0182] Similarly, as can be seen from Table 2, in Examples 101, 108-110, when different monomers are used to form different kinds of polymer thin layers, the internal resistance of the secondary battery in Examples 101, 108-110 is relatively small compared to Comparative Examples 1001-1003.

[0183] As can be seen from the test results of Examples 101, 104 and 105, when the thickness of the second inorganic layer is 5 nm, the internal resistance of the battery is 49.5 mΩ, which exhibits a relatively low internal resistance. This is because the relatively thin second inorganic layer has less effect on the migration path of lithium ions, and the lithium ions can pass through the layer more smoothly, thereby reducing the internal resistance of the battery. As the thickness of the second inorganic layer increases, the migration path of lithium ions in the solid composite film layer gradually becomes longer, and the resistance that needs to be overcome during migration also increases, causing the internal resistance to increase to some extent. In Example 101, the thickness of the second inorganic layer is 10 nm, and the internal resistance increases to 50.2 mΩ, still maintaining a relatively low internal resistance level. When the thickness is further increased, the increasing trend of the internal resistance is more obvious, and in Example 105, the thickness of the second inorganic layer is 20 nm, and the internal resistance increases to 52.1 mΩ. This change reflects that as the thickness of the second inorganic layer increases, the migration path of lithium ions becomes longer, and the resistance that needs to be overcome during transmission increases, thereby causing the internal resistance to increase. However, despite the slight increase in internal resistance, the overall performance of the battery remains relatively stable, which indicates that the design of the solid composite film layer can effectively maintain a low internal resistance within a certain thickness range. Overall, the increase in the thickness of the second inorganic layer has a gradual effect on the internal resistance of the battery, and the magnitude of this change is relatively small, indicating that the solid composite film layer has good stability in optimizing the performance of the battery.

[0184] Both of the examples 101 and 106 use graphite as the negative active material, but the active group 2 of the two examples are different, which are hydroxyl (-OH) and carboxyl (-COOH) respectively. As shown in Table 2, the direct current internal resistance of the example 101 and the example 106 are 50.2 mΩ and 50.0 mΩ respectively, which are very close, indicating that the two different active groups 2 have similar effects on the internal resistance of the battery. For the rate performance, the 2C discharge rates of the example 101 and the example 106 are 85.6% and 85.3% respectively, which also show similar discharge capacities. In addition, the capacity retention rates of the example 101 and the example 106 are 96.2% and 95.8% respectively, which also have very small differences. Therefore, the two active groups 2 have similar effects on the improvement of the battery performance.

[0185] As shown by the test results of the examples 101, 111 and 112, with the increase of the thickness of the polyethylene terephthalate thin layer (polymer layer), the internal resistance of the secondary battery gradually increases. The increase of the thickness of the polyethylene terephthalate thin layer increases the path length of ion migration, thereby increasing the migration resistance of lithium ions in the solid composite film layer. In addition, the polyethylene terephthalate thin layer molecules have a steric hindrance effect, and with the increase of the thickness of the polyethylene terephthalate thin layer, the steric hindrance effect is enhanced, thereby limiting the migration of lithium ions, reducing the ion conductivity, and resulting in the increase of the internal resistance of the secondary battery.

[0186] In the examples 101, 113 and 114, different negative active materials are used respectively: the example 101 uses graphite, the example 113 uses silicon-carbon, and the example 114 uses silicon. As shown in Table 2, The internal resistance of the secondary battery in the example 101 is smaller, and the internal resistance of the secondary battery in the examples 113 and 114 is larger. The reason is that the graphite structure is stable, the volume change during the charging and discharging process is small, the solid composite film layer deposited on the graphite is more stable, and the ion conductivity is better, so the internal resistance of the secondary battery in the example 113 is smaller. In comparison, the negative active materials used in the examples 113 and 114 both contain silicon, and during the charging and discharging process, the volume change of silicon is large, and the solid composite film layer deposited on the silicon (or silicon-carbon) will be deformed to a certain extent, resulting in the increase of the migration path of lithium ions, and thereby resulting in the increase of the internal resistance of the secondary battery.

[0187] The test results of Comparative Examples 101-112 and Comparative Example 1001 show that the rate performance of the secondary battery with the solid composite film layer (i.e., artificial SEI film) deposited on the negative electrode active material layer 1 is superior to that of the secondary battery with the naturally formed SEI film on the negative electrode active material layer 1. In Comparative Examples 101-112 of the present application, the solid composite film layer is formed by a precise deposition process (e.g., atomic layer deposition and / or molecular layer deposition), which makes the structure uniformity of the solid composite film layer better. At the same time, the inorganic layer (e.g., aluminum oxide thin layer) in the solid composite film layer provides higher mechanical strength, which can inhibit the volume change of the negative electrode active material; the polymer layer (e.g., polyethylene terephthalate thin layer) provides better flexibility, which can buffer the volume change of the negative electrode active material. Such a combined structure makes the solid composite film layer not easy to break and can maintain higher stability, thereby maintaining lower internal resistance at high-rate discharge and ensuring better rate performance.

[0188] However, in Comparative Example 1001, the surface of the negative electrode active material layer 1 is a naturally formed SEI film. In the initial stage of charging and discharging of the secondary battery, the naturally formed SEI film is generated by chemical reaction between the electrolyte and the negative electrode active material. Due to the differences in electrochemical reaction conditions (such as current density, local voltage, etc.) in different regions of the secondary battery, the generation rate and composition of the naturally formed SEI film may be different in different regions. Making its thickness, structure and composition non-uniform, leading to poor uniformity of the naturally formed SEI film. The naturally formed SEI film is too thick or too thin in some areas, which will cause the difference in lithium ion migration resistance in different regions. This makes the lithium ions in some regions of the secondary battery unable to quickly enter or leave the negative electrode active material during high-rate charging and discharging, resulting in a decrease in the rate performance of the secondary battery as a whole. Comparative Examples 113 and 1002, and Example 114 and Comparative Example 1003 also conform to the above variation rule.

[0189] Similarly, as described above, the surface of the negative electrode active material layer 1 of the secondary battery in Comparative Examples 1004 and 1005 will also generate a naturally formed SEI film during charging and discharging, which makes the lithium ions in some regions of the secondary battery unable to quickly enter or leave the negative electrode active material during high-rate charging and discharging, resulting in a decrease in the rate performance of the secondary battery as a whole.

[0190] As can be seen from the test results of Examples 101-112 and Comparative Example 1001, when the solid composite film layer (i.e., artificial SEI film) is deposited on the negative active material layer 1, the cycle life (capacity retention rate after 1000 cycles) of the secondary battery is better. In the present application, the solid composite film layer has higher stability, uniformity and ion conductivity, so that the solid composite film layer can effectively reduce the internal resistance and improve the rate performance in a long time of charge and discharge cycle. Compared with the naturally formed SEI film, the solid composite film layer is formed on the surface of the negative active material by precise deposition process (such as atomic layer deposition method and molecular layer deposition method), which forms a more uniform and dense film layer, which not only can effectively prevent the direct contact of electrolyte with the surface of negative active material, reduce unnecessary side reactions, but also can enhance the mechanical strength of the film layer, avoid the film layer rupture caused by volume expansion or thermal stress. In contrast, the naturally formed SEI film often has the problems of thickening, rupture or non-uniformity due to its instability during formation, resulting in poor ion conductivity, large internal resistance, and the film layer is prone to degradation, especially in a long time of charge and discharge cycle, the film layer is prone to rupture or fall off, thereby affecting the electrochemical performance of the secondary battery. In addition, the mechanical strength and thermal stability of the solid composite film layer are also stronger than those of the naturally formed SEI film, which can better adapt to the volume change of the negative active material, prevent the film layer from rupturing or failing during high-rate discharge. Therefore, the solid composite film layer shows better capacity retention rate and longer service life in the long cycle process, effectively improving the cycle stability of the secondary battery. Comparative Example 113 and Comparative Example 1002, and Example 114 and Comparative Example 1003 also conform to the above change rule.

[0191] As can be seen from the test results of Comparative Examples 101-112 and Comparative Example 1001 in Table 2, compared with the secondary battery with naturally formed SEI film on the negative active material layer 1, the secondary battery with solid composite film layer (i.e., artificial SEI film) deposited on the negative active material layer 1 has higher coulomb efficiency. The reason is that the first inorganic layer (such as aluminum oxide thin layer) and the second inorganic layer (such as aluminum oxide thin layer) of the solid composite film layer can provide higher mechanical strength, effectively inhibit the volume change of the negative active material generated in the charge and discharge process. The polymer layer (polyethylene terephthalate thin layer) of the solid composite film layer has a certain flexibility, which has a buffering effect on the volume change of the negative active material. In addition, the second inorganic layer (such as aluminum oxide thin layer) as the outermost protective layer prevents the polymer layer (polyethylene terephthalate thin layer) from reacting with the electrolyte. The first inorganic layer, the polymer layer and the second inorganic layer cooperate with each other, so that the solid composite film layer can effectively resist the volume change of the negative active material, ensure the integrity of the solid composite film layer, reduce the consumption of electrolyte in the charge and discharge process, and thus improve the coulomb efficiency of the secondary battery and prolong the service life of the secondary battery.

[0192] The above merely describes preferred embodiments of the present application, and is not used to limit the present application, any modification, equivalent replacement and improvement made within the spirit and principle of the present application should be included in the protection scope of the present application.

Claims

1. A negative electrode sheet for a secondary battery, characterized in that, A solid composite film layer is deposited on the surface of the negative electrode active material layer, the solid composite film layer comprising a first inorganic layer, a polymer layer, and a second inorganic layer, and the layers of the solid composite film layer are chemically bonded.

2. The negative electrode sheet of a secondary battery according to claim 1, characterized by The thickness of the first inorganic layer is 0.1 nm to 80 nm, the thickness of the polymer layer is 0.4 nm to 100 nm, and the thickness of the second inorganic layer is 0.1 nm to 80 nm.

3. The negative electrode sheet of the secondary battery according to claim 2, characterized by The thickness of the first inorganic layer is 0.5 nm to 20 nm, the thickness of the polymer layer is 2 nm to 60 nm, and the thickness of the second inorganic layer is 0.5 nm to 20 nm.

4. The negative electrode sheet of the secondary battery according to claim 1, characterized by The surface of the second inorganic layer further comprises a repeating unit composed of the polymer layer and the inorganic layer, and the repeating unit is 1 to 50.

5. The negative electrode sheet of a secondary battery according to claim 1, characterized by The first inorganic layer and / or the second inorganic layer comprises an oxide selected from the group consisting of aluminum (Al), titanium (Ti), silicon (Si), tin (Sn), vanadium (V), zirconium (Zr), zinc (Zn), lithium (Li), sodium (Na), potassium (K), niobium (Nb), tungsten (W), molybdenum (Mo), or a combination thereof.

6. The negative electrode sheet of the secondary battery according to claim 5, characterized by The first inorganic layer and / or the second inorganic layer comprises one of the following oxides: aluminum oxide (Al2O3), titanium dioxide (TiO2), silicon dioxide (SiO2), tin dioxide (SnO2), vanadium pentoxide (V2O5), zirconium dioxide (ZrO2), zinc oxide (ZnO), lithium oxide (Li2O), superoxide lithium (LiO2), sodium oxide (Na2O), superoxide sodium (NaO2), potassium oxide (K2O), superoxide potassium (KO2), niobium pentoxide (Nb2O5), tungsten trioxide (WO3), molybdenum trioxide (MoO3).

7. The negative electrode sheet of a secondary battery according to claim 1, characterized by The second inorganic layer comprises one of the following compounds: fluoride, oxide, carbide, and nitride.

8. The negative electrode sheet of the secondary battery according to claim 6, characterized by The first inorganic layer and the second inorganic layer both comprise an aluminum oxide (Al2O3) thin layer.

9. The negative electrode sheet of the secondary battery according to claim 6 or 7, characterized by, The second inorganic layer comprises an aluminum fluoride (AlF3) thin layer.

10. The negative electrode sheet of the secondary battery according to claim 1, characterized by The polymer layer is polymerized from a monomer having multiple functional groups.

11. The negative electrode sheet of the secondary battery according to claim 10, characterized by The monomer is selected from the group consisting of terephthaloyl chloride, ethylene glycol, terephthalamide, terephthaldehyde, terephthalic acid, p-phenylenediamine, hydroquinone, p-chlorobenzene, p-dinitrobenzene, 2,4-dinitroaniline, 4-4'-diaminodiphenyl ether, 4-4'-dihydroxydiphenyl ether, 4-4'-dicarboxy diphenyl ether, 4-4'-dichlorodiphenyl ether, ethylenediamine, oxalic acid, glyoxal, 1,2-dichloroethane, malonyl chloride, pyromellitic dianhydride, and derivatives of the above.

12. The negative electrode sheet of the secondary battery according to claim 11, characterized by The monomer is terephthaloyl chloride and ethylene glycol.

13. The negative electrode sheet of the secondary battery according to claim 11, characterized by The monomer is terephthaloyl chloride and p-phenylenediamine.

14. The negative electrode sheet of the secondary battery according to claim 11, characterized by The monomer is ethylene glycol and p-phenylenediamine.

15. The negative electrode sheet of the secondary battery according to claim 11, characterized by The monomer is terephthaloyl chloride, ethylene glycol, and p-phenylenediamine.

16. The negative electrode sheet of a secondary battery according to claim 1, characterized by An active group is formed on the surface of the negative electrode active material layer, and the active group is chemically bonded to the first inorganic layer.

17. The negative electrode sheet of the secondary battery according to claim 16, characterized by The active group includes one of the following groups: hydroxyl (-OH), carboxyl (-COOH), amino (-NH2), aldehyde (-CHO) and nitro (-NO2).

18. The negative electrode sheet of the secondary battery according to claim 16, characterized by, The active group is hydroxyl (-OH).

19. The negative electrode sheet of a secondary battery according to claim 1, characterized by, The negative electrode active material layer includes one of the following negative electrode active materials: graphite, hard carbon, silicon-carbon composite, silicon-oxygen-carbon material composite, silicon, lithium metal, lithium titanium oxide, silicon-based alloy, tin-based alloy, lithium-based alloy, copper or copper-based alloy, or a combination thereof.

20. The negative electrode sheet of the secondary battery according to claim 1, characterized by, The negative electrode active material used in the negative electrode active material layer includes graphite.

21. The negative electrode sheet of the secondary battery according to claim 1, characterized by, The negative electrode active material used in the negative electrode active material layer includes silicon-carbon composite or silicon-oxygen-carbon material composite.

22. The negative electrode sheet of the secondary battery according to claim 1, characterized by The negative electrode active material used in the negative electrode active material layer includes silicon.

23. The negative electrode sheet of the secondary battery according to claim 1, characterized by, The negative electrode active material used in the negative electrode active material layer is lithium metal.

24. A method for producing a negative electrode sheet of a secondary battery, the negative electrode sheet comprising a negative electrode active material layer, characterized by, A solid composite film layer is deposited on the surface of the negative electrode active material layer by the following steps: S1. introducing an active group on the surface of the negative electrode active material layer by chemical treatment; S2. forming a first inorganic layer on the active group by atomic layer deposition; S3. forming a polymer layer on the upper surface of the first inorganic layer by molecular layer deposition; and S4. forming a second inorganic layer on the upper surface of the polymer layer by atomic layer deposition.

25. The method of producing a negative electrode sheet of a secondary battery according to claim 24, characterized by In step S1, the active group introduced on the surface of the negative electrode active material layer by chemical treatment is selected from one of the following groups: hydroxyl (-OH), carboxyl (-COOH), amino (-NH2), aldehyde (-CHO) and nitro (-NO2).

26. The method of producing a negative electrode sheet of a secondary battery according to claim 24, characterized by In step S1, the chemical treatment is micro-oxidation treatment on the surface of the negative electrode active material layer to introduce a hydroxyl active group.

27. The method of producing a negative electrode sheet of a secondary battery according to claim 26, characterized by In step S1, the micro-oxidation treatment method is plasma oxidation method.

28. The method of producing a negative electrode sheet of a secondary battery according to claim 26, characterized by In step S1, the micro-oxidation treatment method is oxidant oxidation method, and the oxidant used is hydrogen peroxide solution.

29. The method of producing a negative electrode sheet of a secondary battery according to claim 24, characterized by In step S2, the first inorganic layer is prepared by atomic layer deposition (ALD) using water vapor (H2O) and trimethylaluminum (TMA) gas.

30. The method of producing a negative electrode sheet of a secondary battery according to claim 24, characterized by In step S2, the number of deposition cycles of the atomic layer deposition (ALD) of the first inorganic layer is 1-800 times, and the thickness of the first inorganic layer is 0.1 nm-80 nm.

31. The method of producing a negative electrode sheet of a secondary battery according to claim 24, characterized by In step S2, the number of deposition cycles of the atomic layer deposition (ALD) of the first inorganic layer is 5-200 times, and the thickness of the first inorganic layer is 0.5 nm-20 nm.

32. The method of producing a negative electrode sheet of a secondary battery according to claim 24, characterized by, In step S3, the polymer layer is prepared by molecular layer deposition (MLD) using a monomer with multiple functional groups; the monomer is selected from the following monomers: terephthaloyl chloride, ethylene glycol, terephthalamide, terephthaldehyde, terephthalic acid, p-phenylenediamine, hydroquinone, p-chlorobenzene, p-dinitrobenzene, 2,4-dinitroaniline, 4-4'-diaminodiphenyl ether, 4-4'-dihydroxydiphenyl ether, 4-4'-dicarboxy diphenyl ether, 4-4'-dichlorodiphenyl ether, ethylenediamine, oxalic acid, glyoxal, 1,2-dichloroethane, malonyl chloride, pyromellitic dianhydride, and derivatives of the above substances.

33. The method of producing a negative electrode sheet of a secondary battery according to claim 32, characterized by, In step S3, the monomers are terephthaloyl chloride and ethylene glycol, which are polymerized into a polyethylene terephthalate thin layer by a molecular layer deposition method (MLD).

34. The method of producing a negative electrode sheet of a secondary battery according to claim 24, characterized by, In step S3, the number of deposition cycles of the molecular layer deposition method (MLD) of the polymer layer is 1-250, and the thickness of the polymer layer is 0.4 nm-100 nm.

35. The method of producing a negative electrode sheet of a secondary battery according to claim 24, characterized by, In step S3, the number of deposition cycles of the molecular layer deposition method (MLD) of the polymer layer is 5-150, and the thickness of the polymer layer is 2 nm-60 nm.

36. The method of producing a negative electrode sheet of a secondary battery according to claim 32, characterized by, In step S3, the monomers are terephthaloyl chloride and p-phenylenediamine, which are polymerized into a poly(p-phenylene terephthalamide) thin layer by a molecular layer deposition method (MLD).

37. The method of producing a negative electrode sheet of a secondary battery according to claim 32, characterized by, The monomers are ethylene glycol and p-phenylenediamine, which are polymerized into a poly(p-phenylene glycol terephthalamide) thin layer by a molecular layer deposition method (MLD).

38. The method of producing a negative electrode sheet of a secondary battery according to claim 32, characterized by, The monomers are terephthaloyl chloride, ethylene glycol, and p-phenylenediamine, which are polymerized into a poly(p-phenylene glycol terephthalamide) thin layer by a molecular layer deposition method (MLD).

39. The method of producing a negative electrode sheet of a secondary battery according to claim 24, characterized by, In step S4, a second inorganic layer is prepared by an atomic layer deposition method (ALD) using water vapor (H2O) and trimethylaluminum (TMA) gas.

40. The method of producing a negative electrode sheet of a secondary battery according to claim 24, characterized by, In step S4, the number of deposition cycles of the atomic layer deposition method (ALD) of the second inorganic layer is 5-200, and the thickness of the second inorganic layer is 0.5 nm-20 nm.

41. A liquid secondary battery, characterized by comprising: Comprising: The negative electrode tab of the secondary battery of any one of claims 1-23, The positive electrode tab, The separator, and The electrolyte.

42. A semi-solid secondary battery characterized by comprising: Comprising: The negative electrode tab of the secondary battery of any one of claims 1-23, The positive electrode tab, and The semi-solid electrolyte between the positive and negative electrodes.

43. A solid-state secondary battery, characterized by comprising: Comprising: The negative electrode tab of the secondary battery of any one of claims 1-23, The positive electrode tab, and The solid electrolyte between the positive and negative electrodes.

44. The secondary battery of any one of claims 41-43, wherein, The negative electrode active material of the negative electrode active material layer comprises graphite.

45. The secondary battery of any one of claims 41-43, wherein, The negative electrode active material of the negative electrode active material layer comprises a silicon-carbon composite or a silicon-oxygen-carbon material composite.

46. The secondary battery according to any one of claims 41-43, wherein The negative electrode active material of the negative electrode active material layer comprises silicon.

47. The secondary battery of any one of claims 41-43, wherein, The negative electrode active material of the negative electrode active material layer is lithium metal.

48. The secondary battery of any one of claims 41-43, wherein, The positive electrode active material used by the positive electrode tab comprises one of the following compounds: a lithium-containing compound, a sodium-containing compound.

Citation Information

Patent Citations

  • Method for coating negative electrode material and battery

    CN108807855A

  • Lithium ion battery silicon negative electrode material taking lithium-based composite film as protective layer and method

    CN116314733A

  • Weft knit with improved embosser and elasticity and method for preparing thereof

    KR102829089B1

  • Protective coatings for lithium anodes

    US10553874B2

Cited By

  • Battery chip back electrode passivation method

    CN121358047A